The Influence of Boron on Microstructural Evolution, Mechanical and Magnetic Behavior of Amorphous Fe91−x(Zr5-Nb4)Bx Melt-Spun Alloys - Jonathan Zamora; Israel Betancourt; José Alejandro García Hinojosa (Metals, 2022)
In this work, we report a systematic study on the microstructure evolution of rapid solidified Fe91−xZr5Nb4Bx alloys (x = 10, 15, 20, 25, 30 at%) under melt-spinning conditions. Mechanical and magnetic properties are also evaluated. X-ray diffraction patterns indicate that the microstructure across the compositional series consists of an amorphous matrix with partial crystallization when boron concentration is increased. These features were identified by transmission electron microscopy (TEM). The radial distribution function (RDF) affords to resolve the nearest-neighbor configuration. The tensile and microhardness properties were measured to correlate the microstructural evolution with boron content. On the other hand, the magnetic properties of these alloy series were determined by vibrating sample magnetometry (VSM); the saturation magnetization and Curie temperature showed an increasing tendency when increasing the boron content, reaching values up to 110 Am2kg−1 and 465 K, respectively. In addition to the aforementioned, the coercive field remained constant. All these magnetic properties were correlated with the microstructure features observed by XRD, RDF and TEM.